Crossing Francophone Boundaries: Beckett's Fictions - Beryl Schlossman (Studies in 20th & 21st Century Literature, 2002)
Although Samuel Beckett's œuvre is bilingual in French and English, his writing is generally considered to be the product of a single national identity…
Keywords: Samuel Beckett; bilingualism; self-translation; identity; national identity; French criticism; Irish; Irish Renaissance; A Portrait of the Artist as a Young Man; other; outside; malone dies